Percutaneous Penetration Enhancers Physical Methods in Penetration Enhancement - Dragicevic, Nina; I. Maibach, Howard (Springer Berlin Heidelberg : Imprint: Springer, 2017)
Percutaneous Penetration Enhancers in a mini-series format comprising five volumes, represents the most comprehensive reference on enhancement methods - both well established and recently introduced - in the field of dermal/transdermal drug delivery. In detail the broad range of both chemical and physical methods used to enhance the skin delivery of drugs is described. All aspects of drug delivery and measurement of penetration are covered, and the latest findings are provided on skin structure and function, mathematics in skin permeation, and modern analytical techniques adapted to assess and measure penetration. In offering a detailed description of the methods currently in use for penetration enhancement, this book will be of value for researchers, pharmaceutical scientists, practitioners, and also students.
Keywords: Medicine.; Pharmacology.; Dermatology.; elektronické knihy; electronic books